Análisis del Potencial Energético Solar Basado en Mediciones in Situ en el Municipio de Acacías - Meta - Aya, Angel Alejandro Rodriguez; Luna, John Alejandro Figueredo; García, Juan Alejandro Chica (KnE Engineering, 2018)
This research presents the preliminary results of the research entitled Design and implementation of a fixed and mobile photovoltaic system to capture the solar power, determining the cost-benefit ratio for the Acacías CEAD, a study that will determine the solar power that affects the University National Open and Distance - UNAD of the municipality of Acacías and deliver a study to determine the solar radiation of the area, in order to verify the potentiality and feasibility of installing solar energy systems in the University and nearby areas; It has been possible to determine that solar power in the area per m² is close to 45% of that measured by IDEAM (Hydrology, Meteorology and Environmental Studies Institute in Colombia), with a potential absorption of 331W per day in an area of 1m², which makes feasible a possible implementation of a solar energy system. Keywords: Solar power, solar energy, solar panel, energy efficiency.